Plot DIAGRAMS FOR-TO-NEXT IN LANGUAGES ADDITIVE FOR BASIC MATRIX - Hening Hendrato Hendrato (Majalah SIKOMTEK, 2003)
On the computer there is software and hardware. Form of software programs and hardwaredevices such as elektronika.Program on software can be obtained or created using the plotdiagram. Basic language is the beginning of the program / simple compared to otherprograms that exist in software.FOR-TO-NEXT themselves are terms contained in the basic language programs, andincluding the beginning compared to other terms that existed at the basic language courses.Basic language for flowcharts FOR NEXT-TO-try is applied to the sum of the matrix,although considered still nothing compared to the basic language in general.